Presidential Visit: panel session featuring H.E. Dr. Julius Maada Bio and Hafez Ghanem - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Insightful panel discussion, moderated by IITA DG and CGIAR Regional Director for Africa, Dr. Simeon Ehui, featuring His Excellency Dr. Julius Maada Bio, the President of Sierra Leone, and Hafez Ghanem, the former Vice President of the World Bank and a former Assistant Director-General at the FAO. This engaging conversation will offer valuable insights as these esteemed leaders share their perspectives on key issues in African agriculture and engage in a dynamic exchange of ideas.